Classroom Community and Time: Comparing Student Perceptions in Traditional vs. Accelerated Online Courses - Lowenthal, Patrick R.; Trespalacios, Jesús (Online Learning, 2022)
Online educators regularly experiment with ways to create a sense of classroom community in the online courses they design and teach. They do this in part to battle feelings of isolation and loneliness but also to align with prevailing theories of learning (e.g., social constructivism) as well as to mimic idealized in-person face-to-face learning experiences. However, little is known about how well a sense of community is developed in accelerated online courses. Given this, we investigated students’ perceptions of classroom community in traditional length online courses (e.g., 15-week courses) and accelerated online courses (e.g., 7-week courses) taught by the same instructors. The results showed that there was not a statistically significant difference in students’ perceptions of classroom community between the 15-week and 7-week courses. Students in this study rated the accelerated 7-week courses as having a higher sense of classroom community. In this paper, we present the results of our inquiry. We conclude with the implications of our research on research and practice.